Molecular Mechanisms Underlying Cell Death in Spinal Networks in Relation to Locomotor Activity After Acute Injury in vitro - Kuzhandaivel, Anujaianthi; Nistri, Andrea; Mazzone, Graciela L.; Mladinic, Miranda (Frontiers in Cellular Neuroscience, 2011)
Understanding the pathophysiological changes triggered by an acute spinal cord injury is a primary goal to prevent and treat chronic disability with a mechanism-based approach. After the primary phase of rapid cell death at the injury site, secondary damage occurs via autodestruction of unscathed tissue through complex cell death mechanisms that comprise caspase-dependent and caspase-independent pathways. To devise novel neuroprotective strategies to restore locomotion, it is, therefore, necessary to focus on the death mechanisms of neurons and glia within spinal locomotor networks. To this end, the availability of in vitro preparations of the rodent spinal cord capable of expressing locomotor-like oscillatory patterns recorded electrophysiologically from motoneuron pools offers the novel opportunity to correlate locomotor network function with molecular and histological changes long after an acute experimental lesion. Distinct forms of damage to the in vitro spinal cord, namely excitotoxic stimulation or severe metabolic perturbation (with oxidative stress, hypoxia/aglycemia), can be applied with differential outcome in terms of cell types and functional loss. In either case, cell death is a delayed phenomenon developing over several hours. Neurons are more vulnerable to excitotoxicity and more resistant to metabolic perturbation, while the opposite holds true for glia. Neurons mainly die because of hyperactivation of poly(ADP-ribose) polymerase-1 (PARP-1) with subsequent DNA damage and mitochondrial energy collapse. Conversely, glial cells die predominantly by apoptosis. It is likely that early neuroprotection against acute spinal injury may require tailor-made drugs targeted to specific cell death processes of certain cell types within the locomotor circuitry. Furthermore, comparison of network size and function before and after graded injury provides an estimate of the minimal network membership to express the locomotor program.